Assessment of Blood Donation and Transfusion in Eastern Uganda: A Mixed-Methods Study - Laura Checkley; Girish Motwani; Irma Catherine Wange; Obieze Nwanna-Nzewunwa; Fred Kirya; Mary Margaret Ajiko; Catherine Juillard; Rochelle A. Dicker (Ubiquity Press, 2019)
Background: Blood and blood products are essential in the management of injuries, medical illnesses, and childbirth. Chronic shortages in the blood supply perpetuates the high levels of morbidity and mortality from injury and treatable diseases. Patients in low- and middle-income countries are frequently unable to access blood units necessary for transfusion in a timely manner. Objectives: This study aimed to gain insight into the community and hospital factors that contribute to the observed insufficient supply of blood units available for transfusion at a regional referral hospital in rural Eastern Uganda. Methods: A mixed-methods approach was utilized; community members were surveyed on knowledge, attitudes, and practices of blood donation and health professionals were queried on hospital factors affecting blood transfusions. Transfusion records were prospectively collected and analyzed, and the pathway of a single blood unit was observed and recorded. Findings: Among the 82 community members that were surveyed, knowledge was poor (<50% correct) regarding age, weight, and volume of blood to be able to donate, but participants were overall knowledgeable on general characteristics that would exclude individuals from donating blood. Major themes elicited during qualitative interviews included a positive attitude towards and lack of information regarding blood donation. Health professionals expressed frustration in delayed testing of transfusion transmissible infections. The majority of blood transfusions were allocated to female patients (55.8%) and children under five years of age (33.2%). Conclusions: Broadened inclusion and education of the general population in blood donation and increased outreach programs may be promising interventions to increase the blood supply at the Soroti Regional Referral Hospital. To reduce the current bottleneck seen in TTI testing, the feasibility and cost-effectiveness of local TTI testing technology should be investigated further.